Prarancangan Pabrik Fenol Dan Aseton Dari Cumene Menggunakan Proses KBR Dengan Disain Alat Utama Menara Distilasi Fenol (D-106) - Tesa Agustin; Desi Heltina (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The need for phenol and acetone in Indonesia is increasing every year. Based on data from the Central Bureau of Statistics, in the last 5 years, the amount of phenol imports was 20,000 - 26,000 tons/year and the amount of acetone imports was 17,000-22,000 tons/year. Phenol is used as raw material for caprolactam industry, raw material for bisphenol-A whichis used in the manufacture of alkylphenols, phenolic resins, and anilines. While acetone is used as a solvent for waxes, gums, dyes, resins, oils and cellulose. The phenol and acetone factories were designed using the KBR process with cumene as raw material. This plant is planned to operate for 330 days per year and work continuously for 24 hours / day with capacity of 30,000tons / year which will be established in Dumai, Riau. The main tool designed is a phenol distillation tower (D-106) which functions to separate phenol from its mixed compounds. The distillation tower has a height of 10.3548 m and a diameter of 2.286 m with a type of sieve tray distillation and torispherical head with a phenol product purity of 97%. Total Capital Investment for phenol and acetone factories was Rp. 185,258,095,680 with a Fixed Cost value of Rp. 71,474,886,729. The economic analysis of the feasibility of the factory shows that the factory is feasible to build, which can be seen from the analysis of the IRR value obtained of 49.82%, the ROI value of 19.84%, and the pay back period of 4.54 years.Keywords: acetone, cumene, distillation tower, KBR process, phenol